2016
DOI: 10.2172/1239543
|View full text |Cite
|
Sign up to set email alerts
|

Economic Assessment of Hydrogen Technologies Participating in California Electricity Markets

Abstract: As the electric sector evolves and increasing amounts of variable renewable generation are installed on the system, there are greater needs for system flexibility and sufficient capacity, and greater concern for overgeneration from renewable sources not well matched in time with electric loads. Hydrogen systems have the potential to support the grid in each of these areas. However, limited information is available about the economic competitiveness of hydrogen system configurations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 19 publications
0
31
0
3
Order By: Relevance
“…In addition to gas to power (GtP), hydrogen can be marketed as a product for use in chemical industries and hydrogen vehicles. The whole system involves water electrolysis, including alkaline electrolysis, polymer electrolyte membrane (PEM) electrolysis, solid oxide electrolysis (SOEC), and hydrogen storage, which mainly uses compressed gas tanks, cryogenic compressed liquid hydrogen tanks, metal hydride storage, and fuel cells . A typical scheme of a wind‐hydrogen power system is presented in Figure .…”
Section: Scheme Of a Wind‐hydrogen Power System With Clustered Wind Fmentioning
confidence: 99%
“…In addition to gas to power (GtP), hydrogen can be marketed as a product for use in chemical industries and hydrogen vehicles. The whole system involves water electrolysis, including alkaline electrolysis, polymer electrolyte membrane (PEM) electrolysis, solid oxide electrolysis (SOEC), and hydrogen storage, which mainly uses compressed gas tanks, cryogenic compressed liquid hydrogen tanks, metal hydride storage, and fuel cells . A typical scheme of a wind‐hydrogen power system is presented in Figure .…”
Section: Scheme Of a Wind‐hydrogen Power System With Clustered Wind Fmentioning
confidence: 99%
“…While power-to-power represents a valuable configuration to provide long-duration storage (days+), because hydrogen can be stored in large underground reservoirs similar to natural gas, previous studies have shown economic challenges with power-to-power hydrogen storage systems (Eichman, 2016). Therefore, the focus of this report is on power-to-hydrogen (i.e., electricity to hydrogen that is sold as a vehicle fuel or industrial gas) and power-to-gas (i.e., electricity to hydrogen that is injected into the pipeline).…”
Section: Hydrogen System Configurationsmentioning
confidence: 99%
“…The mixed-integer program is coded in GAMS. This model has been used previously for hydrogen grid integration activities and is described in detail (Eichman, 2016). The model has also been used for exploring general energy storage valuation (Eichman, 2015).…”
Section: Optimizing Revenue and Device Operationmentioning
confidence: 99%
See 2 more Smart Citations